Examining the Role of Gender in Career Advancement at the Centers for Disease Control and Prevention - Chen, Zhuo (American Public Health Association, 2010)
During the past decade, efforts to promote gender parity in the healing and public health professions have met with only partial success. We provide a critical update regarding the status of women in the public health profession by exploring gender-related differences in promotion rates at the nation's leading public health agency, the Centers for Disease Control and Prevention (CDC). Using personnel data drawn from CDC, we found that the gender gap in promotion has diminished across time and that this reduction can be attributed to changes in individual characteristics (e.g., higher educational levels and more federal work experience). However, a substantial gap in promotion that cannot be explained by such characteristics has persisted, indicating continuing barriers in women's career advancement.